Pemargan Empu Baradah - Sugriwa, I Gusti Bagus (Yayasan Parisada Hindu Dharma Kabupaten Badung, 1975)
An adaptation of a Balinese palm leaf manuscript known as Baradah carita, listed as no. IVA, 661 in Kantor Kirtya, Singaraja, on Baradah, a Hindu priest in the time of King Erlangga, d. 1049.